(untitled) (Minerva. Revista de Filología Clásica, 2019)
Time in historical narratives is not a mathematical abstraction, but is shaped by events and distributed into periods. After reviewing traditional strategies of periodization, including cycles, the Hesiodic succession of ages, and the early Roman idea of historical decline, this paper examines how two views of historical time –as alternating beween good and bad eras and as a sucession of historical stages corresponding in part to the ages of man- were combined in the work of the neglected historian “Vopiscus” (one of the authors of the Historia Augusta) to produce a new conception of historical periodization.